A New Approach For Removing Talc For Upgrading Molybdenite Ores - X. K. Jiang; H. Ban; J. K. Neathery; T. X. Li; J. M. Stencel (Society for Mining, Metallurgy & Exploration, 1999)
Upgrading molybdenite ore can be technically difficult and expensive if talc is a major impurity in the ore. The layered structure of molybdenite and talc decreases the surface specificity of floatation and suppression agents, thereby making molybdenite ore beneficiation inefficient if under some wet processing methods. However, oxidic talc surfaces may be distinct from the sulfidic or oxysulfidic molybdenite surfaces, such distinction related to electron work functions and/or densities of electron donors/acceptors sites. If such differences are present, the upgrading of finely sized molybdenite ore by dry triboelectrostatic methods may hold advantages over traditional wet methods. We report on the upgrading of molybdenite ore using a laboratory-scale, drytriboelectrostatic beneficiation system. This system employs pneumatic transport conditions to tribocharge, beneficiate and collect the fine molybdenite ore particles. Using this system, two Mo ores were beneficiated under dry conditions without the addition of water or surface modifiers and additives. Beneficiation performance was dependent on the particle size of the feed ore. The surface and particulate morphology and elemental concentrations in the parent feeds and the beneficiated products were examined by scanning electron microscopy (SEM) and optical microscopy. These data, in conjunction with a complete recovery analysis, define some potential advantages of dry, triboelectrostatic beneficiation processing and provide insight into factors controlling molybdenite ore upgrading.